2022
DOI: 10.7554/elife.77274
|View full text |Cite
|
Sign up to set email alerts
|

Pinpointing the tumor-specific T cells via TCR clusters

Abstract: Adoptive T cell transfer (ACT) is a promising approach to cancer immunotherapy, but its efficiency fundamentally depends on the extent of tumor-specific T-cell enrichment within the graft. This can be estimated via activation with identifiable neoantigens, tumor-associated antigens (TAAs), or living or lyzed tumor cells, but these approaches remain laborious, time-consuming, and functionally limited, hampering clinical development of ACT. Here, we demonstrate that homology cluster analysis of T cell receptor (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 66 publications
1
14
0
Order By: Relevance
“…The massive TCR sequences generated by high-throughput and single-cell sequencing techniques have greatly promoted the investigation of T cell immune responses. Recently, by clustering experimentally sequenced TCRs with released epitope-known TCRs, researchers were allowed to identify the antigen specificities of epitope-unknown TCRs associated with autoimmune disease[57], viral infection[58], and cancers[59], making it plausible to utilize TCR sequence repertoires for therapeutic discovery. However, the lack of TCR-pMHC complex structures hinders the optimization of TCRs and the rational design of peptide vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…The massive TCR sequences generated by high-throughput and single-cell sequencing techniques have greatly promoted the investigation of T cell immune responses. Recently, by clustering experimentally sequenced TCRs with released epitope-known TCRs, researchers were allowed to identify the antigen specificities of epitope-unknown TCRs associated with autoimmune disease[57], viral infection[58], and cancers[59], making it plausible to utilize TCR sequence repertoires for therapeutic discovery. However, the lack of TCR-pMHC complex structures hinders the optimization of TCRs and the rational design of peptide vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…[48] TCF7 [49] , IL-7R [49] CD39 neg [50,51] , PD-1 low [52] Tumor-reactive T cells � T cells that present in the tumor microenvironment and recognize cancer-related antigens, such as neoantigens. [53] � Generally considered a highly potent population for anti-tumor immunity. [54] � Some recent studies suggest that these cells may present in non-tumor tissues, such as peripheral blood.…”
Section: Transcriptomic Biomarkers (References) Protein Biomarkers An...mentioning
confidence: 99%
“…Not only was high PD-1 expression associated with a highly exhausted phenotype, but it was also associated with high activation of this subpopulation and tumor specificity ( 83 ). Based on evidence from a publicly available database of melanoma tumor antigen-specific TCR sequences, a previous study determined TCR clonotype clusters and found a marked enrichment of convergent TCR clusters in the CD39 + PD-1 + subpopulation of CD4 + and CD8 + TILs ( 84 ). In addition to defining TSTs using CD39 + PD-1 + in human cancer tissues, researchers also focused on circulating CD39 + PD-1 + CD4 + T cells in patients with human papillomavirus (HPV)-induced tumors, a cell subpopulation enriched with activated HLA-DR + and inducible T cell costimulator (ICOS) + and proliferating KI67 + cells in the peripheral circulation, as well as a high proportion of HPV-specific T cells.…”
Section: Combined Molecular Markersmentioning
confidence: 99%
“…Furthermore, moving beyond these empirical cell phenotypes, the FucoID strategies that employ biochemical labeling and capture tumor antigen-specific T cells hold more promise for clinical applications. In addition, the straightforward approach to estimate TIL enrichment with tumor responsive clones based on the TCR repertoire, at the R&D phase, could greatly facilitate the selection of optimal TIL subsets and the optimization of TIL culture conditions and downstream enrichment procedures, and in clinical applications, it should be possible to estimate tumor-specific TIL abundance at the level of independent tumor samples, before and after culture and/or enrichment ( 84 , 105 , 106 ). In the future, the precise isolation of TSTs from different tumor microenvironments remains a major challenge to be overcome.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%